A mixture of three engineered phosphotriesterases enables rapid detoxification of the entire spectrum of known threat nerve agents. Issue 4 (15th October 2019) - Despotović, Dragana; Aharon, Einav; Dubovetskyi, Artem; Leader, Haim; Ashani, Yacov; Tawfik, Dan S
Abstract: Nerve agents are organophosphates (OPs) that potently inhibit acetylcholinesterase, and their enzymatic detoxification has been a long-standing goal. Nerve agents vary widely in size, charge, hydrophobicity and the cleavable ester bond. A single enzyme is therefore unlikely to efficiently hydrolyze all agents. Here, we describe a mixture of three previously developed variants of the bacterial phosphotriesterase ( Bd -PTE) that are highly stable and nearly sequence identical. This mixture enables effective detoxification of a broad spectrum of known threat agents—GA (tabun), GB (sarin), GD (soman), GF (cyclosarin), VX and Russian-VX. The potential for dimer dissociation and exchange that could inactivate Bd -PTE has minimal impact, and the three enzyme variants are as active in a mixture as they are individually. To our knowledge, this engineered enzyme 'cocktail' comprises the first solution for enzymatic detoxification of the entire range of threat nerve agents.